2021
DOI: 10.3389/fonc.2020.593848
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic TILs: Engineered Tumor-Infiltrating Lymphocytes With Improved Therapeutic Potential

Abstract: Immunotherapy has emerged as an effective and life-changing approach for several types of cancers, both liquid and solid tumors. In combination with traditional treatments such as radiotherapy and/or chemotherapy, immune checkpoints inhibitors have improved prognosis and overall survival of patients with advanced melanoma and many other cancers. Among adoptive cell therapies (ACT), while chimeric antigen receptor T cell therapies have demonstrated remarkable efficacy in some hematologic malignancies, such as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…Along with immunogenicity, studies have shown that inflammatory TIME can also increase patients' response to immunotherapy (33)(34)(35). Reports suggest that CD4+ and CD8+ TILs highly enriched in the tumor are related to a higher response rate after receiving immunotherapy (36,37). Intratumor tumor-associated macrophages (TAMs) can be reprogrammed under the action of TIME and can be switched between the M1 type for antitumor immunity and the M2 type for promoting tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Along with immunogenicity, studies have shown that inflammatory TIME can also increase patients' response to immunotherapy (33)(34)(35). Reports suggest that CD4+ and CD8+ TILs highly enriched in the tumor are related to a higher response rate after receiving immunotherapy (36,37). Intratumor tumor-associated macrophages (TAMs) can be reprogrammed under the action of TIME and can be switched between the M1 type for antitumor immunity and the M2 type for promoting tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating immune cells affect the efficacy of radiotherapy, chemotherapy, or immunotherapy, and thus the prognosis of cancer patients ( 30 32 ). We showed that GAD1, SPP1, and WFS1 were markedly positively correlated with diverse immune cells, including B cells, CD8+T cells, CD4+T cells, macrophages, neutrophils, and dendritic cells in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…TIL products are heterogenous in terms of CD8 + /CD4 + T cell ratios and T-cell differentiation stage and can be impacted by tumor biology ( 164 ). For an endowment of resistance to tumor suppression and/or enhanced tumor homing, TILs can be genetically modified either using different types of vectors or via gene editing technologies ( 165 ).…”
Section: Multicellular Therapiesmentioning
confidence: 99%